The The Role of Fintech Financing and Influencer Marketing on the Marketing Performance of MSMEs with Innovation Product as Variables Mediation - Muhammad Yani; Sriyono Sriyono; Arbiya Magfiroh Rohmi (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of FinTech financing and influencer marketing on MSMEs’ marketing performance, with product innovation serving as a mediating variable. The research is motivated by the growing importance of digital financial access and digital marketing strategies in enhancing MSMEs’ competitiveness, as well as the limited integration of digital finance and digital promotion within a single comprehensive conceptual framework. A quantitative approach with explanatory research design was employed. Data were collected through questionnaires distributed to 109 MSME owners who have utilized FinTech financing and influencer marketing strategies. The data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) with SmartPLS 4.0. The findings indicate that FinTech financing has a positive and significant effect on both marketing performance and product innovation. Influencer marketing does not have a significant direct effect on marketing performance, but it has a positive and significant effect on product innovation. Product innovation significantly enhances MSMEs’ marketing performance. Mediation analysis reveals that product innovation partially mediates the relationship between FinTech financing and marketing performance and fully mediates the relationship between influencer marketing and marketing performance. The R² values indicate strong predictive power, and the model demonstrates high predictive relevance. These findings confirm that digital financial resources and digital promotional strategies do not automatically improve marketing performance unless they are transformed into strategic capabilities through product innovation. This study extends the Resource-Based View (RBV) by integrating digital finance and digital marketing into a resource–capability–performance framework within the MSME context.